2008
DOI: 10.1002/lt.21361
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic cholangiopathy following liver transplantation from donation after cardiac death donors

Abstract: The use of donation after cardiac death (DCD) donor hepatic allografts is becoming more widespread; however, there have been published reports of increased graft failure from specific complications associated with this type of allograft. The complication of ischemic cholangiopathy (IC) has been reported to occur more frequently after the use of DCD hepatic allografts. We report the results of 52 liver transplants from DCD donors and the factors that influenced the development of IC. We conducted a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
193
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(205 citation statements)
references
References 15 publications
(22 reference statements)
8
193
2
2
Order By: Relevance
“…The most important issue regarding this modality is the gap between an insufficient pool of organ donors and the increasing number of potential recipients 1,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important issue regarding this modality is the gap between an insufficient pool of organ donors and the increasing number of potential recipients 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, organs from non heart beating donors (NHBD) can be suitable for transplantation, regardless of a worse first year graft survival outcome 1,2,4,9 . Contemporary aspects of organ donation after cardiac death have stimulated the development of experimental models aiming the improvement of preservation and organ dysfunction 2,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…6,[12][13][14][16][17][18]25,[28][29][30] Foley and coworkers 13 reported that rates of overall biliary complications (DCD, 47%; DBD, 26%; P < .01) and IC (DCD, 34%; DBD, 1%; P < .01) were significantly higher in the DCD group. Research conducted by Chan and associates 28 indicated no incidence of PNF from DCD allografts. Hepatic artery complications and anastomotic bile duct complications were comparable in the 2 groups.…”
Section: Complications Of Livers From Donation After Cardiac Death Domentioning
confidence: 99%
“…Previous publications have sought to identify risk factors for the development of IC in DCD grafts (Table 5). 12,13,28,31 In addition, a higher incidence of intrahepatic bile duct strictures (IHBS) of 16% following DCD liver transplant, compared with 3% in DBD recipients, was recently reported. 29 The DCD recipients had 10.8-fold increased odds of presenting with IHBS.…”
Section: Complications Of Livers From Donation After Cardiac Death Domentioning
confidence: 99%
See 1 more Smart Citation